A quick decrease of bone marrow edema in sacroiliac joint could be served as a novel marker for dose tapering of etanercept in ankylosing spondylitis patients. Issue 11 (March 2019) - Yang, Ruishan; Liu, Hongda; Fan, Mengpo
Abstract : Abstract: The purpose of this study was to investigate the correlation of bone marrow edema (BME) in sacroiliac joint (SIJ) with clinical characteristics and clinical response, and whether the quick decrease of BME could be served as a novel marker for dose tapering of etanercept in ankylosing spondylitis (AS) patients. Ninety active AS patients underwent etanercept treatment for 6 months were enrolled consecutively and classified into standard dose group ( n = 37) and dose tapering group ( n = 53). BME in SIJ and clinical response were assessed by SPARCC criteria and ASAS 40 response criteria, respectively. "Quick decrease of BME in SIJ" was defined as the decrease of SPARCC score≥50% from M0 to M1. BME in SIJ was positively correlated with pain VAS score, BASDAI score, CRP, IL-1β, IL-17, and TNF-α levels. ASAS 40 response rate at M6 was lower in dose tapering group than standard dose group, while higher in patients with a quick decrease of BME in SIJ than other patients. Besides, the ASAS 40 response rate in dose tapering group was similar to standard dose group in patients with a quick decrease of BME in SIJ but was lower than standard dose group in patients without a quick decrease of BME in SIJ at M6. A quick decrease of BME in SIJ predicts better treatment response to etanercept, and it might be served as a novel marker for dose tapering initiation of etanercept in AS patients.